Efeito dos anestésicos inalatórios no transportador de dopamina em fatias de córtex cerebral de ratos - Janice Henriques da Silva (2006)
Inhalatory anesthetics affect synaptic transmission, but little is known about their actions in the central nervous system. Dopamine is a catecholaminergic neurotransmitter that has important functions in the central nervous system and it is possible that its release can be modulated by inhalatory anesthetics. The study of inhalatory anesthetics effects in the neurotransmitter release could provide further information about the mechanisms that contribute with the actions of these agents during anesthesia. In this study, cortical slices of rat brain were labeled with [3H] dopamine to observe the effects of sevoflurane and halothane in the release of this neurotransmitter. Dopamine release was significantly increased in the presence of sevoflurane (0,46 mM) and halothane (0,048 mM) were incubed. This effect was independent of extracellular or intracellular calcium, and it was not affected by TTX (blocker of voltage dependent sodium channels) or reserpine (an blocker of vesicular monoamine transporter). These data suggest that dopamine release induced by anesthetics is independent of the exocytotic process and that this release would be mediated by the dopamine transporter. Experiments using low temperature or by decreasing sodium concentration in the incubation media indicated that dopamine release induced by anesthetics was considerably reduced. The same effect was also observed when dopamine and noradrenaline transporter inhibitors were used (GBR12909 and nisoxetine, respectively). Ouabain, Na+/K+ ATPase pump inhibitor, is known for stimulating dopamine release through the membrane transporter. In its presence, the evoked response by anesthetics was decreased. Nevertheless, further experiments demonstrated that halothane and sevoflurane did not inhibit the Na+/K+ ATPase pump. In conclusion, our study strongly suggests that halothane and sevoflurane increase dopamine release in cortical slices of rat brain and that this release is mediated by the dopamine transporter present in the plasma membrane.